Sturge-Weber syndrome with anomalous venous drainage – An unusual manifestation of neurocutaneous syndrome - Shanki Kaundal,; Mohit Bajaj,; Sandeep Kumar,; Seema Sharma,; Avinash Sharma, (Indian Journal of Case Reports, 2020)
Sturge-Weber syndrome is a rare congenital vascular disorder manifesting with a constellation of signs and symptoms including a facial capillary malformation (port-wine stain), abnormal blood vessels of the brain (leptomeningeal angioma), and associated with abnormal blood vessels of the eye leading to glaucoma. Here, we report the case of an 18-month-old child who had skin lesions on both sides of the face since birth, macrocephaly, left-sided focal seizures, and developmental delay. The child was initiated on carbamazepine at 10 mg/kg/day at admission and the dose was increased to 15 mg/kg/day. On subsequent follow-up, the child is seizure free till now.